A Validated LC-MS/MS Method for Simultaneous Determination of Six Aconitum Alkaloids and Seven Ginsenosides in Rat Plasma and Application to Pharmacokinetics of Shen-Fu Prescription. (28th June 2018) - Ouyang, Huizi; Liu, Fang; Tang, Zhidan; Chen, Xiaopeng; Bo, Fang; Liu, Huaming; Chang, Yanxu; He, Jun
Abstract : A sensitive and reliable LC-MS/MS method has been developed and validated for simultaneous determination of six Aconitum alkaloids (aconitine, hypaconitine, mesaconitine, benzoylaconitine, benzoylhypacoitine, and benzoylmesaconine) and seven ginsenosides (Rb1, Rb2, Rc, Rd, Re, Rf, and Rg1 ) in rat plasma after oral administration of Shen-Fu prescription. Psoralen was selected as internal standard (IS). Protein precipitation with methanol was used in sample preparation. The chromatographic separation was achieved on a CORTECS™ C18 column with 0.1% formic acid aqueous solution and acetonitrile as mobile phase. The flow rate was 0.3 mL/min. The detection was performed on a tandem mass system with an electrospray ionization (ESI) source in the positive ionization and multiple-reaction monitoring (MRM) mode. The calibration curves of six Aconitum alkaloids and seven ginsenosides were linear over the range of 0.1-50 and 1-500 ng/mL, respectively. The extraction recoveries of the analytes in plasma samples ranged from 64.2 to 94.1%. Meanwhile, the intra- and interday precision of the analytes were less than 14.3%, and the accuracy was in the range of −14.2% to 9.8%. The developed method was successfully applied to the pharmacokinetics of six Aconitum alkaloids and seven ginsenosides in rat plasma after oral administration of Shen-Fu prescription.